Establishment and validation of an evaluation system for hospital infection prevention and control courses: a study protocol using the Delphi method and analytic hierarchy process - Mu, Jing; Huang, Qiyuan; Tu, Jiajia; Liu, Fang (Frontiers in Public Health, 2025)
BackgroundThe evaluation of hospital infection prevention and control (HIPC) courses holds significant importance in guaranteeing the quality. Regrettably, there is currently no specific evaluation tool available in China for this purpose. This study aims to develop a comprehensive system to evaluate the HIPC courses in China.MethodsThe authors developed an initial draft for a curriculum evaluation system, based on the context, input, process, and product model, a literature review, and semi-structured interviews with 23 participants. Subsequently, an evaluation system was established via two rounds of Delphi surveys involving 18 experts from 7 A-grade tertiary hospitals and 11 higher medical education institutions across China. The validity of the evaluation system was further confirmed using the Analytic Hierarchy Process (AHP), ensuring a comprehensive assessment of the established framework.ResultsAfter two rounds of correspondence, the evaluation index system includes four first-level indicators, 13 second-level indicators, and 52 third-level indicators. The expert authority coefficients for these rounds were 0.869 and 0.887, respectively, indicating a high level of expertise among the participating experts. Additionally, the Kendall’s W of each index are, respectively, was 0.153 0.162 and 0.168 0.175 (p < 0.05). The consistency test was conducted using the AHP for all judgment matrices, with a consistency ratio (CR) for all levels of indicators < 0.10, indicating good consistency in the weight settings. Among the four first-level indicators, the weight of the “Course Process” was the highest (0.5857), followed by the “Course Product” (0.2389), while the weights for the “Course Context” and “Course Input” were the same (0.0877).ConclusionThe evaluation system for the hospital infection prevention and control courses is CIPP-oriented, comprehensive, and reliable. It offers a practical framework for comprehensively assessing the teaching effectiveness of the courses and enhancing educational quality.